Relevansi Nilai-nilai Aswaja dalam Membentuk Karakter Pelajar di Era Digital - Firdian, Muhammad Syukron Fitra; Winarto (Aksioreligia, 2025)
The digital era has changed human behavior in learning, interacting, and obtaining information. Various challenges arise, such as declining ethics in digital communication, the spread of unverified information, and the erosion of moral values due to the influence of global culture. This study aims to analyze the relevance of the values of Ahlussunnah wal Jama'ah (ASWAJA) in shaping the character of students in the digital era. The approach used is a qualitative approach with a literature study method. The results of the study indicate that the main values of ASWAJA such as tawassuth (moderate), tasamuh (tolerant), tawazun (balanced), i'tidal (fair), and ta'awun (helping each other) have high relevance in shaping the character of students who have noble morals, are adaptive to technological developments, and are able to act wisely in dealing with the rapid and complex flow of information. These values encourage the birth of students who are not only academically capable, but also have moral integrity, good social attitudes, and resistance to the negative influences of digital media. Thus, strengthening ASWAJA values is an important strategy in character education in the modern era and needs to be mandatory material, especially in Islamic religious education subjects.